Expression, characterization, and immobilization of a novel SGNH esterase Est882 and its potential for pyrethroid degradation - Zong, Wei; Su, Wenfeng; Xie, Qingfen; Gu, Quliang; Deng, Xinyi; Ren, Yifei; Li, He (Frontiers in Microbiology, 2022)
The widely-used pyrethroid pesticides have attracted public attention because of their potentials to cause environmental pollution and toxic effects on non-target organisms. Esterase is a kind of hydrolytic enzyme that can catalyze the cleavage or formation of ester bonds. it plays a pivotal role in the decomposition of pyrethroids and esters containing industrial pollutants through the hydrolysis of ester bonds. Here, a new esterase gene est882 was successfully screened, which encodes Est882, a SGNH family esterase composed of 294 amino acids. It was heterogeneously expressed, identified and immobilized. Multiple sequence alignment showed that Est882 had a typical GDS(X) conserved motif and a catalytic triad composed of Ser79, Asp269 and His275. Phylogenetic analysis showed that Est882 shall belong to a new esterase family. Biochemical characterization demonstrated that the optimum condition was 40°C and pH 9.0. Est882 immobilization was studied with mesoporous silica SBA-15 as the carrier and found to significantly improve the tolerance and stability of Est882. Its optimum pH increased to 10.0 and stabilized within pH 8.0–11.0. Free Est882 can effectively degrade various pyrethroids within 30 min, with a degradation rate above 80%. The immobilized Est882 yet degraded more than 70% of pyrethroids within 30 min. The present study indicated that Est882 has outstanding potential in bioremediation of a pyrethroid-polluted environment. These characteristics endow Est882 with potential values in various industrial applications and hydrolysis of pyrethroid residues.